2013
DOI: 10.11622/smedj.2013149
|View full text |Cite
|
Sign up to set email alerts
|

Antenatally diagnosed congenital diaphragmatic hernia in Singapore: a five-year series

Abstract: O r i g i n a l A r tic le 432 I NTRO D U C TIO NCongenital diaphragmatic hernia (CDH), a rare malformation with an incidence of 1.7-5.7 per 10,000 live births, remains one of the most fatal causes of severe respiratory failure.(1,2) CDH was first described by Riveriusin 1672, (3) with the types of defects classified by Morgagni in 1769.(4) The posterolateral defect that we now know as the most common type of CDH was described by Bochdalek in 1848. M E TH O DSAll CDH cases diagnosed antenatally in KKH betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…This is the largest study of CDH patients that we have found in SE Asia. Other smaller SE Asian studies have shown survival of patients ranging from 52-79% [8,[19][20][21][22]. Two of these non-ECMO centers in Taiwan and Singapore, which are high-income countries, report survival to hospital discharge rates of 79% [8,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the largest study of CDH patients that we have found in SE Asia. Other smaller SE Asian studies have shown survival of patients ranging from 52-79% [8,[19][20][21][22]. Two of these non-ECMO centers in Taiwan and Singapore, which are high-income countries, report survival to hospital discharge rates of 79% [8,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, results from these studies could be biased by small numbers of liveborn neonates (n = 24 for both) and may reflect differing antenatal detection rates, termination rates, associated birth anomalies, ease of access to tertiary care facilities, and clinical management. Another study from Singapore found that 46% of cases diagnosed antenatally underwent termination [22]; this may in turn lead to improved survival rates of liveborn neonates with CDH. It is not surprising that of the 52 neonates diagnosed antenatally and referred to our hospital for counselling, none underwent termination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal and foetal mortality rate from acute pancreatitis during pregnancy was reported to be 20%-50%[ 1 ]. The mortality rate from diaphragmatic hernia during pregnancy was 40%[ 2 ]. There have been case reports of congenital Bochdalek hernia and mild acute pancreatitis during pregnancy; however, to our knowledge, there has been only a single case report of congenital Bochdalek hernia complicated with mild acute pancreatitis during pregnancy[ 3 ].…”
Section: Introductionmentioning
confidence: 99%